Instrument unidimensionality, validity and reliability to measure user intention to use of Facebook Cuti-Cuti 1Malaysia - A Manap, Khairulhilmi; Ibrahim, Muhamad Shamsul; Adzharuddin, Nor Azura (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
Facebook users’ motive encourages them to choose the preferred Facebook page. A motive embedded in an individual can be stimulated to become an action. A motive could also turn into motivation during a particular process. This paper's ultimate purpose is to validate the adequacy of the generated items representing the construct involved in this research. The CFA validation included attitude, subjective norms, behavioural control response, Facebook user's experience, response, and engagement. This research collected 237 valid responses from active Facebook users. Upon finding, the attitude is considered invalid as a construct in this research due to the model fit issue. It can be concluded that in general, the remaining items and constructs are considered valid and reliable to be applied in this research and suitable for the second level (measurement model) analysis for validity and reliability.